Policing, Mental Illness and Media: The Framing of Mental Health Crisis Encounters and Police Use of Force, Katrina Clifford (2021). Issue 2 (1st November 2021) - Cullen, Trevor
Review of: Policing, Mental Illness and Media: The Framing of Mental Health Crisis Encounters and Police Use of Force, Katrina Clifford (2021)Cham: Palgrave Macmillan, 347 pp., ISBN 978-3-03061-489-8, h/bk, €89.99ISBN 978-3-03061-490-4, e-book, €76.99